ГРИГОРІЙ САВИЧ СКОВОРОДА. УКРАЇНСЬКИЙ ФІЛОСОФ, ПЕДАГОГ, ПРОСВІТИТЕЛЬ - Зорик, В. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
У цій статті автор прагне дослідити і показати педагогічну діяльність Г.Сковороди наоснові матеріалів і першоджерел. Стаття буде корисна як для студентів і аспірантів, так і длятих, хто займається вивченням спадщини великого українського філософа і просвітителя.В.А. ЗорикГРИГОРИЙ САВИЧ СКОВОРОДА. УКРАИНСКИЙ ФИЛОСОФ, ПЕДАГОГ,ПРОСВЕТИТЕЛЬВ этой статье автор стремится исследовать и показать педагогическую деятельностьГ.Сковороды на основе материалов и первоисточников. Статья будет полезна как для студентови аспирантов, так и для тех, кто занимается изучением наследия великого украинского философаи просвитителя.Ключевые слова: педагогика, просветительство, мир, духовность, Библия, идеализм,мировозрение.THE PEDAGOGICS OF G.I. SKOVORODAV. ZorikIt this article the author attempts himself to investigate and to show the pedagogical activity ofG.Skovoroda on the basis of materials and the ultimate sources. This work will be useful both for thestudents and the graduate students and for the those who deal with the study of the heritage of greatUkrainian philosopher and enlightener.Key words: pedagogics, enlightment, spirituality, Bible, idealism, world view, pantheism.